Efficacy of selected physiotherapeutic methods in conservative therapy of carpal tunnel syndrome - Zwolińska, Jolanta; Kwolek, Andrzej; Skrzypiec, Julian (European Journal of Clinical and Experimental Medicine, 2007)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The carpal tunnel syndrome (CTS) is caused by pressure of the medianus nerve in the carpal canal. The pressure takes place in the event of increase of pressure in the carpal canal or decrease of his volume. The carpal tunnel syndrome cause considerable decrease of patient’s quality of life. The purpose of this study was an evaluation of physiotherapy’s effects in the patients with the carpal tunnel syndrome and the evaluation of the therapy’s effect depending on the parameters of the ultrasonic waves. <span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Material and method. 30 patients with CTS were qualified for the study. 50 hands were examined. In the therapy were used a massage, a neuromobilization of the medianus nerve and ultrasonic waves. The patients were examined before and after the therapy. The study included provocative tests, subjective and objective clinical symptoms and neurophysiological research. The following parameters were assessed: end latency, impulse conduction velocity and evoked response amplitude in medianus nerve. Palmar surface of hand, range of the movement and muscle power were evaluated by using the computer examination. <span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Results. The results of the study show that after using the physiotherapy the pain and the vegetative disorder were decreased in the area of medianus nerve and improvement function the hand. <span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Conclusion. The therapy program is effective. The evaluation of the therapy’s effect depending on parameters of the ultrasonic waves demands farther study.